2020
DOI: 10.1037/dev0000841
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic associations between religiousness and self-regulation across adolescence into young adulthood.

Abstract: Prior research has demonstrated that religiousness is associated with and potentially facilitative of self-regulation, though most of the research has been cross-sectional. The present longitudinal study examined dynamic relations between religiousness development and self-regulation formation from early adolescence into young adulthood. The sample included 500 U.S. adolescents and their parents. The data were restructured by adolescent age and analyzed from ages 11-22. The analyses involved latent curve model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 64 publications
1
14
0
2
Order By: Relevance
“…We suggest that our findings, consistent with the RSM, offer initial support for associations between virtuousness (i.e., humility) and self-regulation (i.e., differentiation and God attachment) as bidirectional (Sandage et al, 2020). Furthermore, Hardy et al (2020) found a bidirectional association over time between R/S and self-regulation, suggesting that gains in R/S might facilitate gains in self-regulation, and conversely, that promoting self-regulation could enhance R/S. Furthermore, Rusk et al (2018) posited that gains in virtuousness and positive emotion reciprocally influence each other.…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that our findings, consistent with the RSM, offer initial support for associations between virtuousness (i.e., humility) and self-regulation (i.e., differentiation and God attachment) as bidirectional (Sandage et al, 2020). Furthermore, Hardy et al (2020) found a bidirectional association over time between R/S and self-regulation, suggesting that gains in R/S might facilitate gains in self-regulation, and conversely, that promoting self-regulation could enhance R/S. Furthermore, Rusk et al (2018) posited that gains in virtuousness and positive emotion reciprocally influence each other.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a longitudinal study with adolescents in Australia revealed that social and emotional well-being, measured in terms of hope, joviality, mindfulness, and psychological acceptance (i.e., willingness to act effectively despite unpleasant thoughts and feelings), was positively associated with intrinsic religious values (Heaven & Ciarrochi, 2007). Another longitudinal study with adolescents in the U.S. found positive bidirectional and cross-lagged relations between religiousness and self-regulation (Hardy et al, 2020), suggesting that self-regulatory abilities and religiousness may sustain each other over time.…”
Section: Religiosity Spirituality and Psychological Well-beingmentioning
confidence: 99%
“…One study of first year college students from two months prior to coming on campus to shortly after arriving found increased use of suppression (Srivastava et al, 2009) whereas another found decreased use of suppression and increased use of reappraisal by the end of the first semester (Kneeland & Dovidio, 2020). Still another study following students from ages 11 to 22 found slight increases in a general measure of emotion regulation (Hardy, Baldwin, Herd, & Kim‐Spoon, 2020).…”
Section: Methodsmentioning
confidence: 99%